A multilayer composite film for an electrode and a method of manufacturing the same
Patent Information
- Application Number
- CN202411498345.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-10-25
AI Technical Summary
这不仅会降低铝箔的机械强度,还会增加其导电性,影响电芯的正常工作
[0025]1.本发明通过使用芳香族聚酯多元醇(聚碳酸酯二醇)与低聚物多元醇(如丁二烯二醇、聚丁二烯-丙烯腈共聚二醇、蓖麻油)的结合,形成既有良好机械性能又具有良好柔韧性的胶水体系,提高了复合膜的整体性能,聚碳酸酯二醇与环氧树脂通过交联反应形成三维网状结构,显著提高胶水的机械强度和耐热性能,增强了复合膜的稳定性和耐用性。
Smart Images

Figure BDA0005101870900000071
Abstract
Description
Technical Field
[0001] This invention belongs to the field of aluminum-plastic film technology, and relates to a multilayer composite film for battery cells, its preparation method, and the preparation method thereof. Background Technology
[0002] Before transporting and processing the battery cells, and after filling them with the battery cells, aluminum-plastic film faces environments with high humidity (≥70% RH) and high temperature (≥30℃). These high humidity and heat conditions pose significant challenges and risks to the performance and structure of the aluminum-plastic film. Aluminum-plastic film is typically composed of multiple layers of composite materials, including nylon layers, aluminum foil layers, and polypropylene cast film layers, bonded together with a composite adhesive. Each layer has a specific response mechanism under high humidity and heat conditions, but the most critical issue lies in the interaction between the nylon layer and the aluminum foil layer.
[0003] First, the nylon layer has a certain degree of water absorption, easily absorbing moisture in high-humidity environments, leading to changes in its physical properties. Nylon's water absorption originates from polar groups in its molecular chains, such as amide groups. These groups can form hydrogen bonds with water molecules, thereby attracting and fixing them. As water molecules gradually aggregate, the interchain spacing of the nylon layer increases, resulting in a decrease in its strength and toughness. This change not only affects the mechanical properties of the nylon layer itself but also adversely impacts its bonding with other layers.
[0004] Secondly, the aggregation of water molecules can penetrate the adhesive layer between the nylon and aluminum foil, damaging the bond between these two materials. The composite adhesive may undergo hydrolysis in high humidity and heat environments, leading to a decrease in its bonding performance. Once the adhesive layer is damaged, the overall performance of the aluminum-plastic film will significantly decline, potentially causing weakened sealing and reduced barrier properties. These problems not only affect the cell's encapsulation but may also cause electrolyte leakage, thus impacting the cell's electrochemical performance and lifespan. Electrolyte leakage can lead to internal short circuits in the battery, and in severe cases, may even cause fires or explosions, posing a threat to user safety.
[0005] Furthermore, high humidity and heat environments can accelerate the oxidation process of aluminum foil, further weakening the protective capabilities of the aluminum-plastic film. Aluminum foil readily reacts with oxygen in humid environments to form an aluminum oxide layer. While the aluminum oxide layer itself provides some protection, under high humidity and heat conditions, it may become porous and lose its protective properties, thus further exposing the aluminum foil to a corrosive environment. This not only reduces the mechanical strength of the aluminum foil but also increases its conductivity, affecting the normal operation of the battery cell. Summary of the Invention
[0006] The purpose of this invention is to address the aforementioned problems in the existing technology by proposing a multilayer composite film for battery cells with excellent heat resistance, which can maintain its excellent performance in high temperature and high humidity environments and will not degrade due to changes in the environment.
[0007] The objective of this invention can be achieved through the following technical solutions:
[0008] A multilayer composite film for battery cells, comprising, from top to bottom, a nylon layer, an aluminum foil layer, and a polypropylene cast film layer, wherein the nylon layer, aluminum foil layer, and polypropylene cast film layer are bonded together with a composite adhesive, wherein the composite adhesive comprises the following raw materials in parts by weight: 70-85 parts aromatic polyester polyol, 5-7 parts oligomeric polyol, 1-5 parts epoxy resin, 5-15 parts tributyl citric acid ester, and 5-10 parts nanocellulose.
[0009] In the aforementioned multilayer composite film used in battery cells, the aromatic polyester polyol is polycarbonate diol.
[0010] In the aforementioned multilayer composite film for battery cells, the oligomeric polyol includes at least one of butadiene glycol, polybutadiene-acrylonitrile copolyol, and castor oil.
[0011] This invention utilizes the combination of aromatic polyester polyols (polycarbonate diols) and oligomeric polyols to form an adhesive system with both good mechanical properties and good flexibility, thereby improving the overall performance of the composite film. Polycarbonate diols and epoxy resins form a three-dimensional network structure through a crosslinking reaction, significantly improving the mechanical strength and heat resistance of the adhesive, and enhancing the stability and durability of the composite film. The combination of oligomeric polyols and epoxy resins forms an adhesive system that is both tough and flexible, further improving the mechanical properties and weather resistance of the adhesive. The combination of tributyl citrate and nanocellulose improves the flexibility and mechanical strength of the adhesive, while also improving the dispersibility of nanocellulose, ensuring its uniform distribution in the adhesive. Epoxy resins and nanocellulose form a denser crosslinked structure through a crosslinking reaction, significantly improving the mechanical strength and heat resistance of the adhesive, while also enhancing its barrier properties to prevent the penetration of water molecules and other harmful substances. The synergistic effect of oligomeric polyols and tributyl citrate improves the flexibility and flowability of the adhesive, while also improving its water resistance and preventing the penetration of water molecules. Ultimately, the composite adhesive of this invention can not only effectively bond the materials of each layer of the multilayer composite film, but also maintain good performance in high humidity and heat environments, ensuring the safety and performance of the battery cell.
[0012] In the aforementioned multilayer composite film for battery cells, the nylon layer surface is coated with PE wax. This PE wax coating significantly improves the surface smoothness of the nylon layer, reduces friction and wear, and increases production efficiency. Simultaneously, the PE wax coating effectively prevents the nylon layers from sticking together during winding or stacking, ensuring smooth delamination of the composite film. Furthermore, the protective film formed by the PE wax reduces scratches and damage to the nylon layer surface, maintaining its integrity and aesthetics.
[0013] In the aforementioned multilayer composite film for battery cells, the concentration of PE wax coating is 1-3 wt%, and the dry adhesive coating amount is 0.1-0.5. By adjusting the coating amount and concentration of PE wax, this invention can optimize the interfacial properties between the nylon layer and the composite adhesive, enhance the bonding strength between the layers of the composite film, and ensure the stability and reliability of the overall performance.
[0014] In the aforementioned multilayer composite film for battery cells, a passivation solution is applied to the surface of the aluminum foil layer. The passivation solution comprises the following raw materials in parts by weight: 20-30 parts acrylic resin, 5-10 parts chromium-containing compound, 0.5-2 parts silane coupling agent, 1-3 parts phosphate, 0.1-0.5 parts sodium polyacrylate, and 60-70 parts deionized water. This invention significantly improves the oxidation and corrosion resistance of the aluminum foil layer by applying a passivation solution. By forming a dense protective film, it prevents oxidation and corrosion of the aluminum foil in high humidity and heat environments, extending its service life. The acrylic resin and silane coupling agent in the passivation solution enhance the bonding strength between the aluminum foil and the composite adhesive, improving the overall stability and durability of the composite film. Simultaneously, sodium polyacrylate acts as a dispersant, ensuring uniform distribution of the components on the aluminum foil surface, forming a smooth coating and improving surface properties. Furthermore, the phosphates and chromium compounds in the passivation solution effectively block the penetration of water molecules and other harmful substances, improving the barrier properties of the aluminum foil, protecting the battery cell from external environmental influences, and ensuring its electrochemical performance and service life. In summary, the aluminum foil coating passivation solution plays multiple positive roles in the preparation of multilayer composite films, improving the overall performance and reliability of the composite film.
[0015] Preferably, the chromium-containing compound is chromic acid. Chromic acid has strong oxidizing properties and can react with the surface of aluminum foil to form a dense chromate protective film.
[0016] Preferably, the phosphate is zinc phosphate.
[0017] Preferably, the silane coupling agent is vinyltrimethoxysilane.
[0018] The present invention also provides a method for preparing the above-mentioned multilayer composite film for battery cells, the method comprising the following steps:
[0019] S1. Apply passivation solution to the surface of aluminum foil, and then use composite adhesive to bond the nylon layer, aluminum foil layer and polypropylene cast film layer together.
[0020] S2, and then proceed with the ripening process;
[0021] S3. After curing and cooling, apply PE wax to the surface of the nylon layer and apply slip powder to the surface of the polypropylene cast film layer. Finally, perform molding and curing.
[0022] In the above-mentioned method for preparing a multilayer composite film for battery cells, the curing temperature in step S2 is 70-85℃ and the time is 3-5 days.
[0023] In the above-mentioned method for preparing a multilayer composite film for battery cells, the molding and curing temperature is 30-40℃ and the relative humidity is 65-75%.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. This invention uses an aromatic polyester polyol (polycarbonate diol) and an oligomeric polyol (such as butadiene diol, polybutadiene-acrylonitrile copolyol, castor oil) to form an adhesive system with both good mechanical properties and good flexibility, thereby improving the overall performance of the composite film. The polycarbonate diol and epoxy resin form a three-dimensional network structure through a crosslinking reaction, which significantly improves the mechanical strength and heat resistance of the adhesive and enhances the stability and durability of the composite film.
[0026] 2. This invention utilizes the combination of tributyl citrate and nanocellulose to improve the flexibility and mechanical strength of the adhesive, while also improving the dispersibility of the nanocellulose, ensuring its uniform distribution in the adhesive. The epoxy resin and nanocellulose form a denser cross-linked structure through a cross-linking reaction, significantly improving the mechanical strength and heat resistance of the adhesive, while also enhancing its barrier properties to prevent the penetration of water molecules and other harmful substances.
[0027] 3. This invention significantly improves the surface smoothness of the nylon layer by applying PE wax, reducing friction and wear, and increasing production efficiency. Simultaneously, the PE wax coating effectively prevents the nylon layers from sticking together during winding or stacking, ensuring smooth delamination of the composite film. Furthermore, the protective film formed by the PE wax reduces scratches and damage to the nylon layer surface, maintaining its integrity and aesthetics. By adjusting the amount and concentration of PE wax, the interfacial properties between the nylon layer and the composite adhesive can be optimized, enhancing the bonding strength between the layers of the composite film and ensuring the overall stability and reliability of the performance.
[0028] 4. This invention provides a detailed preparation method, including coating a passivation liquid onto the surface of an aluminum foil, laminating a nylon layer, an aluminum foil layer, and a polypropylene cast film layer with a composite adhesive, performing a curing treatment, coating the surfaces of the nylon layer and the polypropylene cast film layer with PE wax and slip powder, and finally molding and curing. Strict temperature and time control ensures the high quality and high reliability of the composite film. Detailed Implementation
[0029] The following are specific embodiments of the present invention, which further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.
[0030] Example 1:
[0031] S1. Prepare the following raw materials: 75 parts polycarbonate diol, 6 parts polybutadiene-acrylonitrile copolydiol, 3 parts epoxy resin, 10 parts tributyl citrate, and 8 parts nanocellulose.
[0032] S2. Stir polycarbonate diol and polybutadiene-acrylonitrile copolymer diol, then add epoxy resin, tributyl citrate and nanocellulose in sequence, and then homogenize in a homogenizer at 5000 rpm for 20 min to obtain composite adhesive.
[0033] S3. Prepare the passivation solution according to the following mass proportions of raw materials: 25 parts acrylic resin, 8 parts chromic acid, 1 part vinyltrimethoxysilane, 2 parts zinc phosphate, 0.3 parts sodium polyacrylate, and 65 parts deionized water.
[0034] S4. Apply passivation solution to the surface of aluminum foil, and then use composite adhesive to bond the nylon layer, aluminum foil layer and polypropylene cast film layer together.
[0035] S5. Then, perform a curing process at 80℃ for 4 days.
[0036] S6. After curing and cooling, apply PE wax to the surface of the nylon layer and apply slip powder to the surface of the polypropylene cast film layer. Finally, cure the film at a temperature of 35°C and a relative humidity of 68%.
[0037] Example 2:
[0038] S1. Prepare the following raw materials: 70 parts polycarbonate diol, 5 parts polybutadiene-acrylonitrile copolydiol, 1 part epoxy resin, 5 parts tributyl citrate, and 5 parts nanocellulose.
[0039] S2. Stir polycarbonate diol and polybutadiene-acrylonitrile copolymer diol, then add epoxy resin, tributyl citrate and nanocellulose in sequence, and then homogenize in a homogenizer at 5000 rpm for 20 min to obtain composite adhesive.
[0040] S3. Prepare the passivation solution according to the following mass proportions of raw materials: 20 parts acrylic resin, 5 parts chromic acid, 0.5 parts vinyltrimethoxysilane, 1 part zinc phosphate, 0.1 parts sodium polyacrylate, and 60 parts deionized water.
[0041] S4. Apply passivation solution to the surface of aluminum foil, and then use composite adhesive to bond the nylon layer, aluminum foil layer and polypropylene cast film layer together.
[0042] S5. Then, perform a curing process at 80℃ for 4 days.
[0043] S6. After curing and cooling, apply PE wax to the surface of the nylon layer and apply slip powder to the surface of the polypropylene cast film layer. Finally, cure the film at a temperature of 35°C and a relative humidity of 68%.
[0044] Example 3:
[0045] S1. Prepare the following raw materials: 85 parts polycarbonate diol, 7 parts polybutadiene-acrylonitrile copolydiol, 5 parts epoxy resin, 15 parts tributyl citrate, and 10 parts nanocellulose.
[0046] S2. Stir polycarbonate diol and polybutadiene-acrylonitrile copolymer diol, then add epoxy resin, tributyl citrate and nanocellulose in sequence, and then homogenize in a homogenizer at 5000 rpm for 20 min to obtain composite adhesive.
[0047] S3. Prepare the passivation solution according to the following mass proportions of raw materials: 30 parts acrylic resin, 10 parts chromic acid, 2 parts vinyltrimethoxysilane, 3 parts zinc phosphate, 0.5 parts sodium polyacrylate, and 70 parts deionized water.
[0048] S4. Apply passivation solution to the surface of aluminum foil, and then use composite adhesive to bond the nylon layer, aluminum foil layer and polypropylene cast film layer together.
[0049] S5. Then, perform a curing process at 80℃ for 4 days.
[0050] S6. After curing and cooling, apply PE wax to the surface of the nylon layer and apply slip powder to the surface of the polypropylene cast film layer. Finally, cure the film at a temperature of 35°C and a relative humidity of 68%.
[0051] Example 4:
[0052] The only difference from Example 1 is that the surface of the dragon layer was not coated with PE wax.
[0053] Example 5:
[0054] The only difference from Example 1 is that the surface of the polypropylene cast film was not coated with slip powder.
[0055] Example 6:
[0056] The only difference from Example 1 is that step S5, the ripening process, was not performed.
[0057] Comparative Example 1:
[0058] The only difference from Example 1 is that the raw materials in step S1 do not contain epoxy resin.
[0059] Comparative Example 2:
[0060] The only difference from Example 1 is that the raw materials in step S1 do not contain tributyl citrate.
[0061] Comparative Example 3:
[0062] The only difference from Example 1 is that the raw materials in step S1 do not contain nanocellulose.
[0063] Table 1: Performance test results of the multilayer composite films prepared in Examples 1-6 and Comparative Examples 1-3 after molding in an environment of 50℃ / 80%RH.
[0064]
[0065] In summary, this invention provides a detailed preparation method, including coating a passivation liquid on the surface of an aluminum foil, bonding a nylon layer, an aluminum foil layer, and a polypropylene cast film layer with a composite adhesive, performing a curing treatment, coating the surfaces of the nylon layer and the polypropylene cast film layer with PE wax and slip powder, and finally molding and curing. Through strict temperature and time control, the high quality and high reliability of the composite film are ensured.
[0066] The embodiments described herein cover any points not exhaustively within the scope of the technical claims of this invention, as well as new technical solutions formed by equivalent substitutions of one or more technical features in the embodiments. These are all within the scope of the claims of this invention. Furthermore, in all listed or unlisted embodiments of this invention, each parameter in the same embodiment merely represents an instance (i.e., a feasible solution) of its technical solution, and there is no strict coordination or limitation relationship between the parameters. The parameters can be substituted for each other without violating axioms and the claims of this invention, unless otherwise stated.
[0067] The technical means disclosed in this invention are not limited to those described above, but also include technical solutions composed of any combination of the above technical features. The above descriptions are specific embodiments of this invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of this invention, and these improvements and modifications are also considered within the scope of protection of this invention.
[0068] The specific embodiments described herein are merely illustrative of the spirit of the invention. Those skilled in the art to which this invention pertains may make various modifications or additions to the described specific embodiments or use similar methods to substitute them, without departing from the spirit of the invention or exceeding the scope defined by the appended claims.
Claims
1. A multilayer composite film for use in battery cells, characterized in that, The multilayer composite film comprises, from top to bottom, a nylon layer, an aluminum foil layer, and a polypropylene cast film layer. The nylon layer, aluminum foil layer, and polypropylene cast film layer are bonded together with a composite adhesive, wherein the composite adhesive comprises the following raw materials in parts by weight: 70-85 parts polycarbonate diol, 5-7 parts oligomeric polyol, 1-5 parts epoxy resin, 5-15 parts tributyl citrate, and 5-10 parts nanocellulose. The nylon layer surface is coated with PE wax; The concentration of PE wax for coating is 1-3 wt%; The surface of the aluminum foil layer is coated with a passivation solution, which includes the following raw materials in parts by weight: 20-30 parts acrylic resin, 5-10 parts chromium-containing compound, 0.5-2 parts silane coupling agent, 1-3 parts phosphate, 0.1-0.5 parts sodium polyacrylate, and 60-70 parts deionized water. A slip powder coating is applied to the surface of the polypropylene cast film. The method for preparing the multilayer composite film includes the following steps: S1. Apply passivation solution to the surface of aluminum foil, and then use composite adhesive to bond the nylon layer, aluminum foil layer and polypropylene cast film layer together. S2, and then proceed with the ripening process; S3. After curing and cooling, apply PE wax to the surface of the nylon layer and apply slip powder to the surface of the polypropylene cast film layer. Finally, perform molding and curing.
2. The multilayer composite film for battery cells according to claim 1, characterized in that, Oligomeric polyols include at least one of polybutadiene-acrylonitrile copolyol and castor oil.
3. The multilayer composite film for battery cells according to claim 1, characterized in that, The curing process in step S2 is carried out at a temperature of 70-85℃ for 3-5 days.
4. The multilayer composite film for battery cells according to claim 1, characterized in that, The curing temperature is 30-40℃, and the relative humidity is 65-75%.
Citation Information
Patent Citations
Aluminum-plastic composite packaging film and preparation method thereof
CN110497664A
Reactive adhesive, laminate film, and package
JP2020094154A